Biological studies concerning the antioxidant and antimicrobial activities of Pelargonium species cultivated in Egypt (Family-Geraniaceae) (International Current Pharmaceutical Journal, 2015)
Plant-derived pharmaceuticals have become prominent in the market place, making it a favored healthcare choice. In this study, air dried samples of aerial parts of Pelargonium X fragrans Willd. and Pelargonium peltatum LHérit. were separately extracted using successive extraction with a soxhlet apparatus. Each extract was tested for its antimicrobial activity using two Gram-negative bacterial strains (Pseudomonas aeruginosa and Escherichia coli), two Gram-positive bacterial strains (Bacillus subtillus and Staphyllococcus aureus), and clinical fungal isolates (Aspergillus niger and Candida albicans). Also, their antioxidant activity was tested using a DPPH free radical assay. The ethyl acetate, n-Butanol and the total extracts showed moderate activity against the tested microorganisms with significant high activity against E. coli. The free radical scavenging property was found to be in a concentration dependent manner in all the tested fractions. The most effective antioxidant fractions in both spp. was the n-Butanol fraction (85% and 85.2%) at the concentration of 0.375µg/ml followed by the total ethanolic extracts (78.1% and 84.62%), respectively, with the same concentration compared to the standard reference ascorbic acid which showed a significant radicals scavenging potential (79.1%) in the concentration of 1µg/ml.DOI: http://dx.doi.org/10.3329/icpj.v4i2.21481 International Current Pharmaceutical Journal, January 2015, 4(2): 340-342